The Utility of Synovial Fluid Interleukin-10 in Diagnosing Chronic Periprosthetic Joint Infection: A Prospective Cohort Study - Zou Y; Yang Y; Yang J; Zhang Y; Zhao C; Qin L; Hu N (Infection and Drug Resistance)
Yinshuang Zou,1– 3,* Yaji Yang,1,3,* Jianye Yang,1,3 Yanhao Zhang,4 Chen Zhao,1,3 Leilei Qin,1,3 Ning Hu1,3 1Department of Orthopedics, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People’s Republic of China; 2Department of Orthopedics, Jingzhou Hospital Affiliated to Yangtze University, Jingzhou, 434000, People’s Republic of China; 3Laboratory of Orthopedics, Chongqing Medical University, Chongqing, 400016, People’s Republic of China; 4National Engineering Research Center of Immunological Products, Department of Microbiology and Biochemical Pharmacy, College of Pharmacy, Army Medical University, Chongqing, 400038, People’s Republic of China*These authors contributed equally to this workCorrespondence: Leilei Qin; Ning Hu, Email qinleilei@stu.cqmu.edu.cn; huning@cqmu.edu.cnBackground: Diagnosing chronic periprosthetic joint infection (PJI) is challenging. Synovial fluid interleukin-10 (SF IL-10), an anti-inflammatory cytokine produced by leukocytes, plays a pivotal role in inflammation and infection regulation. However, limited research has explored the diagnostic potential of SF IL-10 in chronic PJI patients.Objective: The study aimed to investigate the relationship between SF IL-10 and incidence of chronic PIJ, and to evaluate its diagnostic reliability.Design and Methods: We analyzed data from 137 patients who underwent revision surgery for aseptic loosening or chronic PJI between 2017 and 2019 in our hospital. PJI diagnoses followed the 2013 International Consensus Meeting criteria. We measured serum ESR, serum CRP, SF PMN%, SF WBC and SF IL-10 levels, using logistic regression and receiver operating characteristic (ROC) curves to evaluate associations and diagnostic accuracy.Results: Demographic data showed no significant differences. However, SF IL-10 levels differed significantly between groups. Logistic regression indicated a strong association between SF IL-10 and chronic PJI (OR = 1.11, 95% CI 1.05~1.17, p < 0.001). At a cut-off of 10.305 pg/mL, SF IL-10 had an area under the ROC curve (AUC) of 0.891, with 92.16% sensitivity and 77.91% specificity. Adding SF IL-10 to traditional models improved risk prediction for chronic PJI (net reclassification improvement [NRI]: 0.167 [0.023 ~ 0.312]; integrated discrimination improvement [IDI]: 0.160 [0.096 ~ 0.224]).Conclusion: Higher SF IL-10 levels were significantly associated with chronic PJI in revision surgery patients, and incorporating SF IL-10 into the traditional risk model enhanced its predictive value for chronic PJI in these patients.Keywords: periprosthetic infection, synovial fluid, interleukin-10, C-reactive protein, erythrocyte sedimentation rate